Didactic Possibilities of Technological Sciences in the Formation of Construction and Technological Competences of Students - Zulaykho Islamovna Juraeva (Genius Journals, 2023)
This article talks about the role of electronic learning tools in the development of constructive and technological competence of secondary school students, directing them to creative thinking and the search for non-standard solutions in this process, and about the didactic possibilities of technological science.
Keywords: Design; student; development of constructive and technological; lesson